Impact of growth of groundwater irrigated area on cropping intensity and crop productivity in Bikaner district of Rajasthan - PRAJAPAT, RAMRAJ; YOGI, VIKRAM; PAREEK, N.K.; SHARMA, SHIRISH (Journal of Soil and Water Conservation, 2022)
The objective of this study is to estimate the groundwater irrigated area growth rates and their impact on cropping intensity and crop productivity in Bikaner district of Rajasthan. The data on canals, tube wells, wells and other sources irrigated area were divided into five decades viz., decade-I (1970-80), decade-II (1980-90), decade-III (1990-2000), decade-IV (2000-10) and decade-V (2010-17). The findings revealed that growth rates of tube wells irrigated area increased significantly at a faster rate than other sources irrigated area in Rajasthan as well as in Bikaner. Cropping intensity and crop productivity have increased as the tube wells and other wells irrigated area as well as the canal and tank irrigated area have increased, but cropping intensity and crop productivity declined as the rain fed area has increased.